Prehospital critical care beyond advanced life support for out-of-hospital cardiac arrest: A systematic review - Adam J. Boulton; Rachel Edwards; Andrew Gadie; Daniel Clayton; Caroline Leech; Michael A. Smyth; Terry Brown; Joyce Yeung (Resuscitation Plus)
Aim: To assess the clinical outcomes of patients with out-of-hospital cardiac arrest attended by prehospital critical care teams compared to non-critical care teams. Methods: This review was prospectively registered with PROSPERO and the eligibility criteria followed a PICOST framework for ILCOR systematic reviews. Prehospital critical care was defined as any provider with enhanced clinical competencies beyond standard advanced life support algorithms and dedicated dispatch to critically ill patients. MEDLINE, Embase and CINAHL databases were searched from inception to 20 April 2024. Risk of bias was assessed using the ROBINS-I tool and the certainty of evidence by the GRADE approach. Meta-analyses of pooled data from studies at moderate risk of bias were performed using a generic inverse-variance with random-effects. Results: The search returned 6,444 results and 17 articles were included, reporting 1,192,158 patients. Three studies reported traumatic patients and one reported paediatric patients. All studies were non-randomised and 15 were at moderate risk of bias. Most studies included prehospital physicians (n = 16). For adult non-traumatic patients, the certainty of evidence was low and prehospital critical care was associated with improved survival to hospital admission (OR 1.95, 95% CI 1.35–2.82), survival to hospital discharge (OR 1.34, 95% CI 1.10–1.63), survival at 30 days (OR 1.56, 95% CI 1.38–1.75), and favourable neurological outcome at 30 days (OR 1.48, 95% CI 1.19–1.84). Prehospital critical care was also associated with improved outcomes for traumatic and paediatric patients and the certainty of evidence was very low. Conclusion: Attendance of prehospital critical care teams to patients with out-of-hospital cardiac arrest is associated with improved outcomes.